Strategi untuk Memperkuat Demokrasi: Studi Kasus Desa Sadar Pengawasan dan Anti Politik Uang di Kabupaten Wajo - Gina Yulianti; Mujibur Rahman Khairul Muluk; Ainul Hayat (Research and Development Agency Ministry of Home Affairs, 2025)
The practice of money politics is eroding the integrity of local democracy in Indonesia, which ranks third worldwide in this phenomenon. This study analyzes the implementation of the “Supervision-Aware Villages and Anti-Money Politics” program in Wajo Regency, South Sulawesi, as a response to the failure of formal institutions to address electoral violations. This study used qualitative methods, collecting data through in-depth interviews with 17 informants from five villages, participant observation, and document analysis, and analyzing them thematically. The findings indicate that the program succeeded in building critical awareness and selective community participation, primarily through the utilization of local norms of siri’ na pacce and the informal leadership of village heads. The synergy between the General Elections Supervisory Agency (Bawaslu), village governments, and communities creates a collaborative oversight space, despite facing structural barriers such as a culture of silence, budget constraints, and the absence of legal protection for whistleblowers. This study extends participatory governance theory by demonstrating that the effectiveness of collaborative governance in regions depends on local cultural norms’ ability to mediate citizen engagement in electoral oversight—a dynamic that clarifies the limits of the theory in contexts with weak formal institutions. Policy implications emphasize the need to institutionalize the program into village governance, integrate it with economic empowerment, and provide adequate whistleblower protection mechanisms to ensure sustainability.